Programa de assistência técnica: Determinante da fidelização do cooperado - Ferreira, Marcelo Bazilio (Universidade do Vale do Rio dos Sinos, 2019)
The present study deals the participation in technical assistance programs as a determinant of the loyalty of rural cooperative milk producers with their cooperative. The theoretical literature and the review of empirical studies are used to formulate the research hypothesis. This hypothesis is tested empirically through econometric procedures, using secondary data from a longitudinal sample of associated who marketed milk with a group of cooperatives from Rio Grande do Sul between 2014 and 2018, resulting in 28,765 observations. Two tests are carried out to verify if there is a difference between the means of loyalty and non-loyalty, the T and Mann-Whitney tests. After verifying that there are statistical differences between the means of the two groups, we try to test the hypothesis using a Logistic Regression test. For robustness, Random-Panel Dashboard tests are used. In all the regressions we observe a positive effect on loyalty for the cooperatives members participating in the technical assistance program. It is concluded that the results confirm the hypothesis that rural cooperative milk producers who participate in the technical assistance program offered by cooperative governance in the State of Rio Grande do Sul are more loyal. Moreover, the use of secondary data, that represents precision and accuracy of the measurements, as well the longitudinal characterization of the research, analyzing the behavior of the same associated for 5 years. This characteristics demonstrates the rigor in the realization for the research and, therefore, reliability of the results.
Keywords: Oportunismo; Governança Cooperativa; Fidelização; Opportunism; Cooperative Governance; Loyalty; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis